Wrzuceni w dolinę – wrzuceni w ciało. O uwikłaniach w egzystencję (Czesław Miłosz "Dolina Issy") - Woźniak, Kamila (Slavia Centralis, 2020)
This outline refers to The Issa Valley, a novel by Czeslaw Milosz. The author raises issues connected with the concept of the valley as a paradise and argues with that concept. She also points out the permanent features of the piece, which are themes of loneliness, transience, the search for God and man not accepting his fate. The center of gravity rests, however, on the profiles of select characters, who find themselves in some kind of existential suspense and are somehow cast into a life that seems foreign and imposed on them.
Keywords: Polish prose; existence; myth-biographism; God; transcendence